Levofloxacin and Tobramycin for Severe Bacterial Keratouveitis. (2nd September 2016) - Accorinti, Massimo; Colao, Lorena; Gilardi, Marta; Cecere, Michela; Salotti, Alessandra; Pesci, Francesca Romana
Abstract: Purpose : To report on clinical features and outcome of severe bacterial keratouveitis. Methods : Twenty patients with severe bacterial keratouveitis treated with topical tobramycin and levofloxacin and oral levofloxacin were included. Main outcome measures were ulcers location, bacterial isolates, risk factors, visual prognosis. Results : Centrally located ulcer/abscess was present in 65% of patients. Contact lens (CL) wear was the most common risk factor (70%). Bacterial isolates were observed in 58% of patients, none resistant to tobramycin and levofloxacin. Pseudomonas aeruginosa was found in 47% of positive cases and in 64% of CL wearers. After therapy, the mean visual acuity improved significantly ( p  < 0.0001), particularly in contact lens wearers ( p  = 0.04) and in patients younger than 60 years old ( p  < 0.001). Conclusions : Pseudomonas aeruginosa is the most frequent cause of bacterial keratouveitis and CL wear the most common risk factor. Topical tobramycin and levofloxacin and oral levofloxacin are effective in the treatment of bacterial keratouveitis.